Downstream grain‐size changes associated with a transition from single channel to anabranching. Issue 5 (25th March 2018) - Morón, Sara; Amos, Kathryn J.
Abstract: Downstream variation in grain size associated with changes in river pattern is a topic that interests multiple disciplines. How grain size varies between adjacent reaches with strongly contrasting river pattern is an outstanding question. This study presents a combined field and numerical modelling investigation of a river with a downstream planform change from single channel to anabranching, where the planform is controlled by a change in underlying lithology. This approach enabled exploration of the controls on sedimentology in a river for which there is very limited opportunity to collect flow and sediment transport data. This study shows that the surficial grain size decreases as a result of the downstream change in planform. This is because of a decrease in flow velocity and shear stress associated with a decrease in channel depth related to the planform change. Channel geometries in both the field and modelling data fit into distinct groups based on channel depth, the deepest being the single channel reach and the shallowest being the anabranching. This downstream reduction in channel dimension (depth) is caused because the total discharge is split from one channel into multiple channels. The coarsest grain sizes (cobble) are deposited at the terminus of the single channel and in the distributary channels; anabranching channels contain sand‐size sediments. This study shows that, in a transition from single channel to anabranching, the channel dimensions decrease as the number of channels increases, resulting in a decrease in bed shear stress and the fining of bed material downstream.